Impact of surgery on quality of life of Ugandan women with symptomatic pelvic organ prolapse: a prospective cohort study - Kayondo, Musa; Kaye, Dan Kabonge; Migisha, Richard; Tugume, Rodgers; Kato, Paul Kalyebara; Lugobe, Henry Mark; Geissbüehler, Verena (BMC Women’s Health, 2021)
Background: Pelvic organ prolapse (POP) is a significant public health issue that negatively affects the Quality of Life (QOL) of women in both low and high-income countries. About 20% of women will undergo surgery for POP over their lifetime. However, there is a paucity of information on the effect of surgery on QOL especially in resource-limited settings. We therefore assessed the QOL among women with symptomatic POP living in rural southwestern Uganda and the impact of surgery on their quality of life. Methods: We conducted a prospective cohort study among 120 women with symptomatic POP scheduled for surgery at the urogynecology unit of Mbarara Regional Referral Hospital. The QOL at baseline and at 1 year after surgery in the domains of physical performance, social interaction, emotional state, sexual life, sleep quality, personal hygiene and urinary bladder function was determined using a King’s Quality of Life questionnaire. A paired t-test was used to compare the difference in mean scores at baseline and at 1-year post-surgery. Results: Of the 120 participants that were enrolled at baseline, 117(98%) completed the follow-up period of 1 year. The baseline QOL was poor. The domains with the poorest QOL were physical, social, sexual, emotional and sleep quality. The mean QOL scores in all the domains and the overall QOL significantly improved 1 year after surgery (p < 0.001). The overall QOL improved by 38.9% after surgery (p < 0.001). Conclusions: The QOL was poor among women with symptomatic POP and surgery improved the QOL in all the domains of life. We recommend that surgery as an option for treatment of symptomatic POP should be scaled up to improve on the QOL of these women.
Keywords: Mbarara; Impact; Pelvic organ prolapse; Quality of life; Surgery